Dentro o más allá de la ayuda: el difícil camino de la Coherencia de Políticas para el Desarrollo - Gutiérrez-Goiria, J.; Millán-Acevedo, N.; Marttínez-Martínez, I (Revista Iberoamericana de Estudios de Desarrollo)
Analyses of Policy Coherence for Development (PCD) began to arise in the OECD more than two decades ago. These approaches have evolved while the discussions about the necessary reform of the system of international cooperation were taking place. However, the meetings in Rome, Paris, Accra and Busan, and the Aid Effectiveness Agenda, focused on a technocratic and unilateral vision of efficiency, away from the approach of CPD. Subsequently, the creation of the Global Partnership for Effective Development Cooperation has not meant a change of course on this issue. The article shows the striking absence of the CPD at conferences and declarations, which contrasts with its remarkable evolution in the doctrinal level, and raises the potentialities of the 2030 Agenda for the CPD.